Pengaruh Kepemimpinan Transaksional, Motivasi, dan Disiplin Kerja Terhadap Kinerja Karyawan pada PT. Sun Star Motor - Linda Dwi Ichromi; Kasmari Kasmari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Every company depends on human resources who play an important role in being able to achieve company goals. The success of a company can be reflected in the performance of the company's employees. The purpose of this study is to find out what is the influence of transactional leadership, motivation and work discipline on employee performance at PT. Sun Star Motor MT. Haryono Semarang by sampling using a saturated sample technique because the entire population was sampled because the number was too small, namely 60 people. This data collection method is researched using the questionnaire method. The variable measurement scale used is the assessment likert scale in the form of a score on answer preferences. The data analysis used was multiple linear regression analysis. In this study, there are three hypotheses that must be tested to prove their suitability for each independent variable to the bound variable. (1) Transactional leadership towards employee performance. For the value of sig. 0.042 < 0.05 with a coefficient of β=0.278 which is a positive value. (2) Motivation for employee performance. For the value of sig. 0.611 > 0.05 with a coefficient of β=-0.077 which is negative. (3) Work discipline has a positive effect on employee performance. For the value of sig. 0.037 < 0.05 with a coefficient of β=0.300 which is a positive value. So the results of the research that have been carried out can be found that transactional leadership has a positive and significant effect on employee performance, motivation has a negative and insignificant effect on employee performance, work discipline has a positive and significant effect on employee performance.